The phenolic compounds of ethanolic extract of date seed (Phoenix dactylifera L.) exert hepatoprotective activity on rat induced carragenan - Warsinah Warsinah; Esti Dyah Utami; Hanif Nasiatul Baroroh (Universitas Islam Indonesia, 2022)
Background: Hepatotoxic effects can occur with the use of toxic drugs or standard doses, but in the long term or chronic therapy. In addition to the drugs, carrageenan also causes hepatotoxic after 12 hours of induction intraperitoneally. The effect of liver cell repair is highly related to the antioxidant activity of phenolic compounds in date seeds.Objective: The present study determined the total phenolic levels and hepatoprotective activity of ethanol extracts of date palm seeds (EEBK) in carrageenan-induced rats.Method: Determination of total phenolics in palm ethanol extract samples was carried out with the Folin- Ciocalteu reagent. This study was the pre and post-test control group design. Examination of SGOT and SGPT levels was performed by the kinetic method based on IFCC. Data was analyzed using paired t-test and ANOVA test. Results: The total phenolic content of the ethanol extract of date seeds of Deglet Noor variety was 8.521% GAE. The ethanol extract of date seed (EEBK) with the dose of 150 mg/kg BW showed the highest reduction in SGOT levels (34.80 U / L). The highest average decrease in SGPT levels occurred at a therapeutic dose of 300 mg/kg BW was 16.20 U / L compared to doses of 150 and 600 mg/kg bb (11.60 and 15.60 U / L respectively).Conclusion: The ethanol extract of date seed (EEBK) with the doses of 150, 300, and 600 mg/kg BW had hepatoprotective activity in carrageenan-induced rats as observed from a significant decreased in SGOT and SGPT levels (p <0.05). Key word: Date seed, phenolic total, extract, SGPT, SGOT